Weeding the nettles I: Clarifying species limits in perennial, rhizomatous Urtica (Urticaceae) from southern and central Chile and Argentina - Weigend, Maximilian; Luebert, Federico (Phytotaxa, 2009)
Several taxa of perennial, rhizomatous Urtica have been described from Chile and Argentina but recent floristic treatments treat these inconsistently. Rhizomatous taxa of Urtica from southern and central Chile and Argentina are here revised based on field and cultivation studies, together with a revision of herbarium material, including the type collections. The application of names to the herbarium material revised, indicates the need for clear morphological species limits within these taxa. These we provide here. A total of three species of perennial, rhizomatous Urtica are recognised for southern and central Chile and Argentina, Urtica magellanica, U. mollis and U. dioica subsp. dioica. Urtica magellanica is here defined to include both U. pseudodioica and U. bracteata [≡ U. magellanica subsp. bracteata ] which are here placed in synonymy. A lectotype for U. buchtienii is designated and U. mollis is here defined to include U. buchtienii which we believe to represent an early season, high-altitude form of the same taxon. Urtica dioica subsp. dioica has been confused with U. magellanica and U. bracteata in the past and we here report it for the first time fromChile andArgentina. Diagnostic characters are tabulated and illustrated, and a key for identifying the three species is provided.